Flexible metallized carbon nanofibers decorated with two-dimensional NiGa2S4 nanosheets as supercapacitor electrodes - Kim, Yongil; Samuel, Edmund; Joshi, Bhavana; Park, Chanwoo; Lee, Hae-Seok; Yoon, Sam S. (Chemical Engineering Journal, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Herein, high-power flexible supercapacitor electrodes were fabricated by decorating Ni-electroplated carbon nanofibers (Ni@CNF) with two-dimensional NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> nanosheets. The electrical conductivity of carbon nanofibers was enhanced by the addition of nickel, and the energy storage capability was enhanced by decoration with NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The impact of metal (Ni/Ga) ratio on the overall electrochemical performance of the supercapacitor was studied by varying the Ga concentration. The NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> nanosheets promoted diffusion of the electrolyte into the electrode, thereby improving the electrochemical activity. The nanosheets also intensified the charge transfer rate within the composite electrode, which contributed to the overall improvement in the electrochemical performance. The optimal Ga concentration was the concentration at which the specific capacitance was the highest at 488 F·g<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">−1<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> with a potential window of 1.1 V and current rate of 0.5 A·g<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">−1<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The long-term stability test revealed that the capacitance retention of the electrode with this optimal Ni/Ga ratio was 109% after 20,000 cycles. This flexible supercapacitor electrode was subjected to 2000 bending cycles, and the corresponding cyclic voltammetry performance was assessed. In combination, the outstanding electrochemical performance and durable mechanical properties render the NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/Ni@CNF electrode highly suitable for flexible energy storage applications.

Formation of zircon-type DyCrO4 and its magnetic properties - Ughade, Supriya; Joshi, Bhavana; Poddar, Pankaj (Ceramics International, 2022)
The formation mechanism of hydrolytic sol-gel synthesized DyCrO4 with a complexing agent in acidic and basic mediums is thoroughly studied. The role of complexing agents and pH on phase formation temperature is also intensively investigated. The formation temperature for DyCrO4 is similar to 500 degrees C in the absence and presence of complexing agents such as oxalic acid and ethylenediaminetetraacetic acid (EDTA) at pH 10. When critic acid is used, the DyCrO4 forms with Cr2O3 impurity. The crystallite size in the presence of a complexing agent in the basic medium is similar to 55 nm which is small as compared to only ammonia solution. The various reaction modes lead to tetragonal zircon-type DyCrO4 at similar to 500 degrees C, transforming into orthorhombic perovskite DyCrO3 at 800 degrees C. The magnetization curve shows the ferromagnetic behavior of DyCrO4 below transition temperature T-c similar to 21 K. This low T-c makes nanocrystalline DyCrO4 a potential material for cryogenic applications.
Keywords: Complexing agent; DyCrO4; Formation mechanism; Hydrolytic sol-gel method; pH

Ferroelectric polarization and iron substitution synergistically boost electrocatalytic oxygen evolution reaction in bismuth oxychloride nanosheets - Singh, Dinesh; Joshi, Bhavana; Poddar, Pankaj (Langmuir, 2023)
Ferroelectric materials have gained significant interestin variouskinds of water splitting, but the study of ferroelectric materialsfor electrocatalytic water splitting is in its infancy. Ferroelectricmaterials have spontaneous polarization below their Curie temperaturedue to dipolar alignment, which results in surface charges. In 2Dferroelectric materials, spontaneous polarization depends on thickness.Herein, we report that thickness-dependent ferroelectric polarizationin 2D nanosheets can also accelerate the oxygen evolution reaction(OER) along with the tailored active surface area of exposed crystallinefacets, which improves the electrocatalytic activity relatively. Iron-substitutedBiOCl nanosheets of varying thickness are fabricated by varying thepH using a facile coprecipitation method. The substituted iron enhancespolarization and electrochemical active sites on the surface. Thefindings in this study show that the exposed (001) facet and higherthickness of the nanosheets have high ferroelectric polarization and,in turn, superior electrocatalytic activity and remarkable stability,requiring low overpotentials (348 mV and 270 mV at 100 mA/cm(2) and 10 mA/cm(2)) in alkaline (1.0 M KOH) electrolyte. Asthe thickness of the nanosheets is decreased from 140 to 34 nm, theelectrocatalytic performance of iron-substituted BiOCl nanosheetsstarts to reduce due to the lower Coulomb-Coulomb interactionand the increasing depolarization.